simplified that would be
It is the same as: 2s = t
2s-4 equals 2(s-2). You can find the answer by factoring two out of both numbers.
2s - 12 + 2s = 4s - 124s - 12 = 4s - 124s = 4ss = s==========this is an identity and any number can be s
2s + s + 12 =132 ie 3s = 132 -12 3s = 120 s = 40
s = 7, t = -3
3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)
2s + 16 = 4s - 6 Subtract 2s from both sides: 16 = 2s - 6 Add 6 to both sides: 22 = 2s divide both sides by 2: s = 11
6s+2s=72 combine like terms 6s+2s=8s set equal to 72 8s=72 divide both sides by 8 to solve for "s". 8s=72 8 8 your answer is s= 72/8 which is 9.
2s + 17 = 2s + 17 1) First, you want to start on the left side of the equation and subtract 17 from both sides. 2s = 2s 2) Then, you take the 2 on the left side and divide it on both sides. s = s 3) You are left with s (Or 1s) on both sides, so s = 1.
It simplifies to: 2s+4R
2s + 5 [ge] 49 (ge stands for "greater than or equal to")2s [ge] 44 s [ge] 22 That is, s is greater than or equal to 22.